Conceptual development of nature of science in biology education: A hybrid bibliometric and SLR analysis - Ghani Walandipa; Hafizah Khaerini; Slamet Suyanto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: The Nature of Science (NOS) is a central concept in science and biology education because it helps students understand how scientific knowledge is developed and supports scientific literacy. However, many NOS studies focus primarily on empirical research trends without integrating conceptual and philosophical perspectives. Objectives: This study aims to analyze the conceptual development of NOS in biology education through an integrated research approach. Methods: A hybrid approach combining bibliometric analysis and systematic literature review (SLR) was employed. Bibliometric data were retrieved from the Scopus database covering publications from 2000–2025 (cut-off: 8 November 2025). From an initial dataset of 35 articles, 11 studies were selected based on predefined inclusion and exclusion criteria. Results: The results show a significant increase in NOS research since 2010. Key themes include evolution, scientific literacy, epistemology, and textbook representation, while argumentation, intelligent design, epistemic practices, and Two-Eyed Seeing perspectives emerge as developing topics. The SLR findings indicate that NOS is understood as a multidimensional concept involving epistemological, pedagogical, and socio-cultural dimensions. Conclusion: This study highlights the importance of integrating philosophical perspectives and authentic representations of scientific practice to strengthen scientific literacy in biology education